Initial clinical results with the ThermoCool® SmartTouch® Surround Flow catheter. Issue 8 (4th October 2016) - Gonna, Hanney; Domenichini, Giulia; Zuberi, Zia; Norman, Mark; Kaba, Riyaz; Grimster, Alexander; Gallagher, Mark M.
Abstract: Aim: The Biosense Webster ThermoCool ® SmartTouch ® Surround Flow (STSF) catheter is a recently developed ablation catheter incorporating Surround Flow (SF) technology to ensure efficient cooling and force sensing to quantify tissue contact. In our unit, it superseded the ThermoCool ® SF catheter from the time of its introduction in May 2015. Methods and results: Procedure-related data were collected prospectively for the first 100 ablation procedures performed in our department using the STSF catheter. From a database of 654 procedures performed in our unit using the SF catheter, we selected one to match each STSF procedure, matching for procedure type, operator experience, patient age, and gender. The groups were well matched for patient age, gender, and procedure type. Procedure duration was similar in both groups (mean 225.5 vs. 221.4 min, IQR 106.5 vs. 91.5, P = 0.55), but fluoroscopy duration was shorter in the STSF group (mean 25.8 vs. 30.0, IQR 19.6 vs. 18.5, P = 0.03). No complication occurred in the STSF group. Complications occurred in two cases in the SF group (one pericardial effusion requiring drainage and one need for permanent pacing). Complete procedural success was achieved in 98 cases in the STSF group and 94 cases in the SF group ( P = 0.15). The composite endpoint of procedure failure or acute complication was less common in the STSF group (2 vs. 8, P = 0.05). Conclusion: The STSF catheter is safe and effective in treating a range of arrhythmias. Compared with the SF catheter, it shows a trend towards improved safety–efficacy balance.